Survei Kepadatan Jentik Nyamuk Aedes Aegypti di Rt 002 Dusun Al-Muhajirin Desa Tulehu Kecamatan Salahutu Kabupaten Maluku Tengah - Kansman Lestaluhu; M Fadly Kaliky (Jurnal Ventilator, 2024)
Dengue, or what people often call dengue fever, is a viral infectious disease that is transmitted through mosquitoes. The incidence of dengue has increased significantly worldwide in recent decades. Dengue has become a public health problem in the world, not only in Indonesia. In early 2020, WHO listed dengue as a global health threat among 10 other diseases. By the end of 2022 the number of dengue cases in Indonesia will reach 143,000 cases, dengue cases occur equally in women (49%) and men (51%). Most dengue cases occur in the 15-44 year age group (39%). This pattern is different from deaths due to dengue, which are more dominant in women (55%) and in the younger age group, namely 5-14 years (45%). Cases of Dengue Hemorrhagic Fever (DHF) in 2021 have doubled compared to the same period in 2020, which was only 41 cases. DHF cases in the city of Ambon have experienced a significant increase, as of June 2021 there were 81 cases of dengue fever recorded with 2 patients dying. The highest number of dengue fever cases was in Sirimau sub-district with 43 cases, followed by Nusaniwe with 18 cases, Baguala with 11 cases, South Leitimur with 6 cases, and Teluk Ambon sub-district with 3 cases. Based on data from the Tulehu Community Health Center, Salahutu District, Central Maluku Regency. There were 11 cases of dengue fever from 2022 to September 2023. Among them, there was 1 case of dengue fever in RT 002 Al-Muhajirin Hamlet, Tulehu Village, Salahutu District, Central Maluku Regency. The type of research used in this research is descriptive research to calculate the percentage of houses positive for Aedes aegypti and calculate the density of larvae in water reservoirs inside and outside people's houses in RT 002 Al-Muhajirin Hamlet, Tulehu Village, Salahutu District, Central Maluku Regency. The results of the research that has been carried out show that RT 002 Al-Muhajirin Hamlet, Tulehu Village, Salahutu District, Central Maluku Regency, the HI index has a Density Figure (DF) of 8 so it is in the high density category, while the CI Index has a Density Figure (DF) of 9 so it is in the high density category.